Reactions of 4-Benzoyl-5-[(E)-2-phenyl-1-ethenyl]-2,3-dihydro-2,3-furandione with Aromatic Aminonucleophiles - Durmaz, Nuri; Onal, Zulbiye; Altural, Behzat (Asian Journal of Chemistry, 2010)
4-Benzoyl-5-[(E)-2-phenyl-1-ethenyl]-2,3-dihydro-2-,3-furandione (1) reacts with various aminonucleophiles (2a–g) and gives the hexadienoic acid derivatives (6-phenyl-3-benzoylarylamino-2-oxo-3,5-hexadieonic acids) (3a–g). The structures of the synthesized compounds were determined by being interpreted by their elemental analysis and IR, 1H- and 13C-NMR spectra.